The Impact of Production Center Policy on Bali Cattle Farming in Southeast Sulawesi, Indonesia: A Policy Analysis Matrix Approach - Rindayati, W.; Gerhana; Priyarsono, D. S. (Tropical Animal Science Journal, 2025)
Implementing government policies aims to enhance Bali cattle farming and exports while protecting domestic production to ensure competitiveness against imported cattle and meat. This study aims to analyze the impact of production center policy on Bali cattle farming in Southeast Sulawesi, Indonesia, using the Policy Analysis Matrix (PAM) approach. Data were collected from June to October 2024 through direct interviews with 240 cattle farmers, field surveys, and focus group discussions with relevant stakeholders. This involved discussions with policymakers in Bali cattle development centers in Southeast Sulawesi, specifically in the regency of South Konawe and Muna. The collected data were analyzed using the PAM. The analysis was conducted per average number of cattle reared and then converted to per cow, with farmers using a combined breeding and fattening system for 12 months (1 year) to produce slaughter-ready cattle. . The results showed that the government policy’s impact on output had a negative effect on Bali cattle farming, as the domestic output price was lower than the world price. The policy’s impact on input had a positive effect, as the government supported producers through input subsidies and protection of domestic input prices, which created additional surplus for farmers, protected domestic production, and reduced input costs. The policy’s combined impact on both input and output also had a positive effect, as it provided incentives for farmers, generated additional surplus, effectively protected production, and lowered production costs compared to opportunity costs. The study concluded that government policy was more beneficial through its support on input and combined input-output interventions than on output alone. Therefore, government policies remain key in regulating Bali cattle development in Southeast Sulawesi to maintain competitiveness and benefit farmers.